ANALISIS KELENGKAPAN PENGISIAN DOKUMEN INFORMED CONSENT PERSFEKTIF HUKUM DI RS PROVINSI LAMPUNG 2013 - Umi Romayati Keswara; Wahid Tri Wahyudi; Ria Aryani (Holistik Jurnal Kesehatan, 2019)
Background: Hypertension or high blood pressure desease is a condition in which an increase in blood pressure above normal. The number of hypertension in the world reaches about 970 million people, 330 million are in deve loped countries and developing countries. Preliminary data shows the incidence of hypertension in Metro City in 2016 reached 1,839 cases and in Metro Public Health Center reached 274 cases. Hypertension is one of the most important causes of early death because it is closely related to the risk of cardiovascular disease. One effort to reduce blood pressure among hypertensive patients is by consuming high potassium fruits such as watermelon. The purpose of this research was to find out the influence of watermelon to reduce blood pressure in patients with hypertension in working area of Central Metro Public Health Center 2017.Methods: This was a quantitative research, the form of pre experimeni design through one group pretest approach. Population in this research was the patients with hypertension 89 people, samples were 35 people. This research analysis was through Paired T Test.Results: The statistic test showed that the mean of blood pressure of hypertensive patients before (pre-test) administration of watermelon was 175.49 / 113.71 fruits with standard deviation 13,678 / 9,16 and after (post-rest) administration of watermelon 137.20 / 90,06 mmHg with Standard deviation 8,380 / 6,268. The result of analysis with paired sample t-test obtained p-value 0,000 <α 0.05 it can be concluded that there is an influence of watermelon to reduce blood pressure of patients with hypertension, where the mean of blood pressure of hypertensive patient after being given treatment significantly lower the blood pressure than before . It is advisable for hypertensive patients, they should be able to maintain high intake of fruit diet, especially that contain high water and potassium.